Proceedings of the International Conference on Communication and Signal Processing 2016 (ICCASP 2016) 2017
DOI: 10.2991/iccasp-16.2017.27
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Machinability of AISI 4340 Steel with Coated Carbide Inserts

Abstract: Abstract:Turning is widely employed as a material removal process for roughing or semi-finishing operation. However, turning of a workpiece material needs use of an appropriate cutting tool insert. Insert material and its geometry play quite significant role in obtaining desired machinability. For obtaining better finish of machined surface, nose radius also plays an important role. In the present work, two coated carbide cutting tool inserts with two different nose radii of 1.2 mm and 1.6 mm are used under tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(7 reference statements)
0
2
0
1
Order By: Relevance
“…Studi yang dilakukan oleh Shalina Sheik Muhammad dkk ialah pengaruh gaya pemotongan permesinan end milling pada material baja AISI 4340 dimana kondisi pendinginana kering dan cryogenic (Muhamad et al 2019). Selain itu AISI 4340 juga diteliti tentang kemapuan mesin dalam pemotongan dengan memperhatikan jenis insert coated carbide (Das, Das, and Mandal 2017). Pada umumnya, material baja AISI 4340 sering dibahas proses pemotongan dengan memvariasikan parameter pemotongan permesinan pada CNC untuk mengetahui hasil pemotongan yang optimal (Lubis et al 2019).…”
Section: Pendahuluanunclassified
“…Studi yang dilakukan oleh Shalina Sheik Muhammad dkk ialah pengaruh gaya pemotongan permesinan end milling pada material baja AISI 4340 dimana kondisi pendinginana kering dan cryogenic (Muhamad et al 2019). Selain itu AISI 4340 juga diteliti tentang kemapuan mesin dalam pemotongan dengan memperhatikan jenis insert coated carbide (Das, Das, and Mandal 2017). Pada umumnya, material baja AISI 4340 sering dibahas proses pemotongan dengan memvariasikan parameter pemotongan permesinan pada CNC untuk mengetahui hasil pemotongan yang optimal (Lubis et al 2019).…”
Section: Pendahuluanunclassified
“…Machining of hard steel materials (hardness between 45 and 68 HRC) at high speeds, feed rate, or depth of cut results in severe tool wear owing to high heat generation at the tool-chip interface, surface integrity issues of the workpiece, etc. (Awale and Inamdar, 2015), (Das et al, 2017). One such hard material widely used in the industrial front is the AISI 4340 steel, which is a type of Ni-Cr-Mo steel material (also known as medium carbon steel) and is known for its good toughness and strength (yield and tensile).…”
Section: Introductionmentioning
confidence: 99%
“…An analytical wear model formulated by Cao et al 42 considering the characteristics of intermittent grinding of a grinding edge, effects of wheel profile on the tool wear, and the number of active grinding edges. Das et al 43 observed that the production of continuous chips (flat) is obtained with a 1.2 mm nose radius at a cutting speed of 147 m/min at a 0.05 mm/rev feed rate. Adopting the CNC lathe machine Gundarneeya et al 44 used EN24 (817M40T) along with a cubic boron nitride tool for the hard part turning process.…”
Section: Introductionmentioning
confidence: 99%